Political and economic governance: a comparative analysis of Eastern European countries and Ukraine - Латковська, Тамара Анатоліївна; Латковська, Т. А.; Латковская, Тамара Анатольевна; Latkovska, Tamara A.; Біла-Тіунова, Любов Романівна; Біла-Тіунова, Л. Р.; Била-Тиунова, Любовь Романовна; Bila-Tiunova, Liubov R. (Baltija Publishing, 2019)
The presented work is an attempt to compare the quality of governance in non-EU states in the Western Balkans and Eastern Europe with which the EU Association Agreements have been concluded, and Ukraine, including aspects of the impact of the DCFTA (Deep and Comprehensive Free Trade Areas). The most important issues are the interpretation of the results, the equality of countries, and the political consequences that may arise after the progression and the rapid pace of the member countries of the DCFTA towards the countries of the Balkan region. The identified countries seek full membership in the EU. Although the EU distinguishes between these countries, it recognizes “European prospects”, that is, membership in the EU, the commitments to adopt or approach EU laws and policies, made by both groups of countries, have much in common. This makes the comparison between the countries of the Balkan region and the member states of the DCFTA a sound and politically significant one. Such comparison is facilitated by numerous sources, qualitative assessments, and official ratings. Figuratively by analytical indicators, the countries can be divided into the first group of leading countries (Serbia and Montenegro) for which in February 2018 the European Commission proposed to consider 2025 as the possible date of accession to the EU. The second group (Albania and Macedonia), for which the date of accession negotiations is conditionally open in 2019. The third group includes Bosnia and Herzegovina, Kosovo, for which there are no dates, and Turkey, the negotiations with which are suspended. For comparison, if we take both political and economic indicators of Ukraine, it is approximately equal to the Balkan states of the second group and outstrips the states of the third group. The prospect of EU membership was recognized as the strongest external factor of internal political changes in the countries surrounding the EU. One of the most striking trends is the steady decline in the standards of political governance in all countries, for which the EU expands its membership perspective. One of the main manifestations of poor governance in the broader neighbourhood is the widespread corruption and impunity of officials. Weak rule of law and ineffective law enforcement bodies have become common practice in all different states and have allowed current officials to act impunity during their term of office. The identified results challenge the assumption dominating in political and scientific circles that a credible prospect of EU membership is steadily generating an internal environment conducive to democratic changes. The effectiveness of economic governance was assessed by the indicators of competitiveness of the national economy (Global Competitiveness Index, Corruption Perceptions Index, Human Development Index, Ease of Doing Business Index, Index of Economic Freedom, Index of Globalization, SEDA (Sustainable Economic Development Assessment)); GDP dynamics; the volume of foreign direct investment; economic activity of the population. In practice, the EU applies an increasing number of common economic policy instruments for the Balkans and member countries of the DCFTA, in spite of the political (or rhetorical) differentiation between countries, given the categorization of membership prospects. The convergence of the actual EU policy has taken place. The Association Agreements and the DCFTA have raised the level of political and economic governance in Georgia, Moldova, and Ukraine at the level of the Balkan countries while the expansion process for the Balkan countries has not advanced.

Представлена ​​робота є спробою порівняти якість управління в державах, що не входять до ЄС, на Західних Балканах і в Східній Європі, з якими були укладені Угоди про асоціацію з ЄС, та в Україні, включаючи аспекти впливу DCFTA (Поглиблена та всеохоплююча зона вільної торгівлі). Найважливішими питаннями є інтерпретація результатів, рівність країн і політичні наслідки, які можуть виникнути після прогресу та швидких темпів країн-членів DCFTA до країн Балканського регіону. Визначені країни прагнуть повноправного членства в ЄС. Хоча ЄС розрізняє ці країни, визнає «європейські перспективи», тобто членство в ЄС, зобов’язання прийняти або наблизити національне законодавство до законів і політики ЄС, взяті обома групами країн, мають багато спільного. Це робить порівняння між країнами Балканського регіону та державами-членами DCFTA обґрунтованим і політично значущим. Такому порівнянню сприяють численні джерела, якісні оцінки та офіційні рейтинги. Образно за аналітичними показниками країни можна поділити на першу групу провідних країн (Сербія та Чорногорія), для яких у лютому 2018 року Єврокомісія запропонувала вважати 2025 рік можливою датою вступу до ЄС. Друга група (Албанія і Македонія), для якої умовно відкрита дата переговорів про вступ у 2019 р. До третьої групи входять Боснія і Герцеговина, Косово, для якої немає дати, і Туреччина, переговори з якою призупинені. Для порівняння, якщо взяти і політичні, і економічні показники України, то вона приблизно дорівнює балканським державам другої групи і випереджає держави третьої групи. Перспектива членства в ЄС була визнана найсильнішим зовнішнім чинником внутрішньополітичних змін у країнах, що оточують ЄС. Однією з найяскравіших тенденцій є постійне зниження стандартів політичного управління в усіх країнах, для чого ЄС розширює перспективи членства. Одним із головних проявів поганого врядування в околицях є поширена корупція та безкарність чиновників. Слабке верховенство права та неефективні правоохоронні органи стали звичайною практикою в усіх різних штатах і дозволили нинішнім чиновникам діяти безкарно під час свого перебування на посаді. Виявлені результати ставлять під сумнів припущення, що домінує в політичних і наукових колах, що вірогідна перспектива членства в ЄС неухильно створює внутрішнє середовище, сприятливе для демократичних змін. Ефективність економічного управління оцінювали за показниками конкурентоспроможності національної економіки (Індекс глобальної конкурентоспроможності, Індекс сприйняття корупції, Індекс людського розвитку, Індекс простоти ведення бізнесу, Індекс економічної свободи, Індекс глобалізації, SEDA (Sustainable Economic Development Assessment). )); динаміка ВВП; обсяг прямих іноземних інвестицій; економічна активність населення. На практиці ЄС застосовує все більшу кількість інструментів спільної економічної політики для Балкан і країн-учасниць ГВЗВТ, незважаючи на політичну (чи риторичну) диференціацію між країнами, враховуючи категоризацію перспектив членства. Відбулося зближення фактичної політики ЄС. Угоди про асоціацію та DCFTA підвищили рівень політичного та економічного управління в Грузії, Молдові та Україні на рівні балканських країн, тоді як процес розширення для балканських країн не просунувся.
Latkovska T. Political and economic governance: a comparative analysis of Eastern European countries and Ukraine / T. Latkovska, L. Bila-Tiunova // Baltic Journal of Economic Studies. - Vol. 5. - № 3. - Baltija Publishing, 2019. - Р. 91-98.
Keywords: European studies; DCFTA; political governance; economic governance; Baltic States; democratic choice; Європейські дослідження; DCFTA; політичне управління; економічне управління; країни Балтії; демократичний вибір; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science